2016
DOI: 10.3390/w8080338
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection and Attribution of Runoff Variations in the Aksu River Basin

Abstract: Abstract:Since the flow variations of Aksu River are strongly influenced by climate change and human activities which threat the local ecosystem and sustainable development, it is necessary to quantify the impact degree of the driving factors. Therefore, this study aims to quantify the impacts of climate change and human activities on the variability of runoff in the Aksu River Basin. The Mann-Kendall trend test and accumulative anomaly method were used to detect the break points of the flow difference value (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…The role of climate change is found to be much greater than land use change [50]. Meng et al used the SWAT model to study the Aksu River in the northwest inland area and found that climate factors and human activities were responsible for 92.28% and 7.72% of the variability, respectively [61]. These are consistent with the results of this paper.…”
Section: Contribution Of Land Use and Climate Change To Runoff Variationsupporting
confidence: 88%
“…The role of climate change is found to be much greater than land use change [50]. Meng et al used the SWAT model to study the Aksu River in the northwest inland area and found that climate factors and human activities were responsible for 92.28% and 7.72% of the variability, respectively [61]. These are consistent with the results of this paper.…”
Section: Contribution Of Land Use and Climate Change To Runoff Variationsupporting
confidence: 88%
“…The SWAT model is a physically distributed hydrological model that has been widely used to assess the impacts of climate change and human activities on water [37,45]. To simplify the watershed and facilitate calculation, the study area was divided into 22 subbasins with 271 hydrologic response units (HRUs) based on land use, soil type, and slope.…”
Section: Hydrological Modelingmentioning
confidence: 99%
“…In addition, extreme precipitation events may be the main cause of extreme flow, especially in Summer. Therefore, we performed a comparison of the probability distributions to assess the performance of the GCMs in simulating precipitation events [36,37]. For each GCM runs, extreme precipitation sequence were extracted based daily precipitation series, and when the precipitation bigger than 0.1 mm/day were selected as a wet day [35].…”
Section: Downscaling Of Future Climate Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies [6,[10][11][12][13][14][15] on current and future water resources in Central Asia have been conducted to gain a deeper understanding of the complex hydrological processes of the region. These studies also intend to gauge, through both statistical analysis on historical data and hydrological modeling, how the area's water resources might change in the coming years.…”
Section: Introductionmentioning
confidence: 99%